PENGARUH KONSENTRASI DAN FREKUENSI APLIKASI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KUBIS (Brasicca oleracea var. capitata) - Numba, Sudirman; Robbo, Anwar; Rahman K., Abd. (Percetakan Umi Toaha Makassar, 2024)
Liquid Organic Fertilizer is a plant fertilizer that comes from organic materials. Raw materials come from wet organic materials or organic materials that have a high water content such as fruit and vegetable waste. POC has a good long-term effect on the soil, namely, it can improve the structure and organic content of the soil, and produce agricultural products that are safe for health so that POC can be used as environmentally friendly fertilizer. The research was carried out from August to October 2020, in Pasa' Dalle Tongko Village, Baroko District, Enrekang Regency. The research aims to determine the best concentration and frequency of POC treatment for the growth and production of cabbage plants. The research was prepared using a factorial design consisting of 2 factors. The first factor is the concentration of POC fertilizer with 3 levels, namely 1 mL/ L of water, 2 ml/ L of water, and 3 mL/ L of water. The second factor is the frequency of POC treatment which consists of 3 levels, namely 2 times spraying, 4 times spraying,and 6 times spraying. The results of the research showed that the interaction of various concentrations and frequency of POC spraying had no significant effect on all parameters observed. POC concentration of 3 mL/ L of water gave significantly different effects on all observation parameters, except for plant height. Similarly, the frequency of spraying 4 times gave a significantly different effect on all observation parameters